A novel rGO-decorated ZnO/BiVO4 heterojunction for the enhancement of NO2 sensing properties. Issue 4 (22nd January 2020) - Bai, Shouli; Tian, Ke; Han, Ning; Guo, Jian; Luo, Ruixian; Li, Dianqing; Chen, Aifan
Abstract : A novel ZnO/BiVO4 /rGO composite exhibits excellent gas sensing performance, which is attributed to the formation of n–n heterojunctions and decoration with rGO. Abstract : A ZnO/BiVO4 heterojunction has been first prepared by the co-precipitation and hydrothermal methods; then, rGO nanosheets are decorated onto the heterojunction by simple hydrazine hydrate reduction to construct a novel ZnO/BiVO4 /rGO composite-based NO2 sensor. The structure, morphology and gas sensing performance of the composite were characterized and measured using various spectroscopies and gas sensing tests. Compared to the same kinds of gas sensors reported previously, this sensor exhibits competitive sensing performance with a maximum response of 126.64 to 1 ppm NO2 at an operating temperature of 95 °C, which is 5.7 times and 2.4 times higher than those of the ZnO and ZnO/BiVO4 junctions, respectively. Also, the sensor shows a rapid response and long-term stability to NO2 compared with pure ZnO. The good sensing properties are ascribed to the formation of the n–n heterojunction between ZnO and BiVO4 and the decoration with rGO.